HERIYADI HARIS: BIOGRAFI DAN PROSES KREATIF DI SANGGAR PERPEKINDO - Khairuz Zulfa; Gita Kinanthi Purnama Asri Adinda; Dewi Rukmini Sulistyawati (TANDIK : Jurnal Seni dan Pendidikan Seni, 2021)
Abstract: This study aims to (1) describe Heriyadi Haris' life history as a dance artist, (2) describe Heriyadi Haris' creative process as a dance artist at Sanggar PERPEKINDO and (3) describe Heriyadi Haris' works and achievements as a dance artist. used is a qualitative method. Data collection techniques using observation, interviews and documents. The research results obtained are. (1) Heriyadi Haris' journey as a dance artist has been quite unique for 40 years, the change of profession from being an athlete to being a dance artist was due to an interest in art since his childhood, according to him, dance is not limited by age and has a certain beauty that is able to elevate the name of his own region. In 1981 he joined the PERPEKINDO studio, his persistence made himself a dancer to a choreographer and even became the leader of the group in 2003. (2) The character in his creative process is influenced by his communicative, cooperative personality and always involves members of the PERPEKINDO studio. Through 4 stages, namely preparation, incubation, illumination and verification or evaluation. (3). In 2011 he received the Borneo Award as a dance artist in South Kalimantan. The dance works that have been created are always based on local culture, either Banjar or Dayak in South Kalimantan. Around 40 works, of which have received various achievements and are displayed at the regional, national and international levels.